2021
DOI: 10.1038/s41467-020-20315-9
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of obesity-associated disorders by a small-molecule drug targeting mitochondria of adipose tissue macrophages

Abstract: Pro-inflammatory activation of adipose tissue macrophages (ATMs) is causally linked to obesity and obesity-associated disorders. A number of studies have demonstrated the crucial role of mitochondrial metabolism in macrophage activation. However, there is a lack of pharmaceutical agents to target the mitochondrial metabolism of ATMs for the treatment of obesity-related diseases. Here, we characterize a near-infrared fluorophore (IR-61) that preferentially accumulates in the mitochondria of ATMs and has a thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 66 publications
(33 reference statements)
0
37
0
Order By: Relevance
“…It is well known that the mitochondrion is the main source of ROS formation, as well as a major target of ROS [ 182 ]. Oxidative stress is closely related to mitochondrial dysfunctions induced by As.…”
Section: Molecular Mechanisms Of Metal-induced Mitochondrial Dysfunctionmentioning
confidence: 99%
“…It is well known that the mitochondrion is the main source of ROS formation, as well as a major target of ROS [ 182 ]. Oxidative stress is closely related to mitochondrial dysfunctions induced by As.…”
Section: Molecular Mechanisms Of Metal-induced Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Accordingly, a conspicuous secretion of these factors is observed in obesity conditions (139,140). Nowadays, obesity represents a global health problem and constantly increases in all countries of the world (141,142). It has been demonstrated that overweight and obesity correlate with the onset of several solid tumors, including esophagus, pancreatic, colon, breast, endometrium, ovarian and kidney, suggesting an association between these conditions and tumor initiation (143,144).…”
Section: Adipocyte-released Factors Strengthening Csc Chemotherapy Refractorinessmentioning
confidence: 99%
“…Obesity environment subjects adipose tissue to transformations resulting in increased size (hypertrophy) and number (hyperplasia) of adipocytes, an infiltration by immune cells, and the development of low-grade chronic inflammation and fibrosis (Vasileva et al, 2018). The described changes define different types of stress such as oxidative, metabolic and mechanical existing in the adipose tissue, which trigger the disbalance in intraand intercellular communication during obesity (Vasileva et al, 2020a;Wang et al, 2021;Zaghlool et al, 2021). Modulation of the adipogenic differentiation is among the most attractive strategies in obesity management (Aprile et al, 2018;Mandl et al, 2019;Rebollo-Hernanz et al, 2019;Vasileva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the activation of AKT stimulates glucose transporter 4 (GLUT4) translocation, increase the glucose influx and the lipogenesis in adipocytes (Lee et al, 2017;Huang et al, 2018;Cignarelli et al, 2019;Liu et al, 2019;Huang et al, 2021). These stimulatory signals are processed by the key players CCAAT-enhancer-binding proteins (C/EBPs), peroxisome proliferator-activated receptors (PPARs), and sterolregulatory-element-binding protein (SERBP) and their downstream targets responsible for lipid biosynthesis such as fatty acid synthase (FASN) and acetyl-coA carboxylase (ACC) to transform the precursor cell into a mature adipocyte (Kim et al, 2018;Vasileva et al, 2018;Cignarelli et al, 2019;Mandl et al, 2019;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%